mTOR Mysteries: Nuances and Questions About the Mechanistic Target of Rapamycin in Neurodegeneration - Norwitz, Nicholas G.; Querfurth, Henry (Frontiers in Neuroscience, 2020)
The mechanistic target of rapamycin protein complex, mTORC1, has received attention in recent years for its role in aging and neurodegenerative diseases, such as Alzheimer’s disease. Numerous excellent reviews have been written on the pathways and drug targeting of this keystone regulator of metabolism. However, none have specifically highlighted several important nuances of mTOR regulation as relates to neurodegeneration. Herein, we focus on six such nuances/open questions: (1) “Antagonistic pleiotropy” – Should we weigh the beneficial anabolic functions of mTORC1 against its harmful inhibition of autophagy? (2) “Early/late-stage specificity” – Does the relative importance of these neuroprotective/neurotoxic actions change as a disease progresses? (3) “Regional specificity” – Does mTOR signaling respond differently to the same interventions in different brain regions? (4) “Disease specificity” – Could the same intervention to inhibit mTORC1 help in one disease and cause harm in another disease? (5) “Personalized therapy” – Might genetically-informed personalized therapies that inhibit particular nodes in the mTORC1 regulatory network be more effective than generalized therapies? (6) “Lifestyle interventions” – Could specific diets, micronutrients, or exercise alter mTORC1 signaling to prevent or improve the progression neurodegenerative diseases? This manuscript is devoted to discussing recent research findings that offer insights into these gaps in the literature, with the aim of inspiring further inquiry.